Therapeutic termination of pregnancy at Instituto Nacional Materno Perinatal , Peru, 2009-2013 - Guevara Ríos, Enrique (2016)
Objective: To determine causes of medical termination of pregnancy at a national maternal perinatal institute. Design: Descriptive observational study. Setting: Instituto Nacional Materno Perinatal, Lima, Peru. Material: Applications for therapeutic termination of pregnancy. Method: Review of all applications for medical termination of pregnancy performed at the institution between 2009 and 2013. Main outcome measures: Medical reasons for therapeutic termination of pregnancy. Results: During the study period 64 applications for medical termination of pregnancy were submitted to the General Director of the Institute; 61 were approved by the Medical Board: one in 2009, one in 2010, four in 2011, 21 in 2012 and 34 in 2013. The mean age of patients was 30.4 years (19-47 years); most patients had one or two previous deliveries (47%); 69% had no history of previous abortion, and the majority (31 cases, 51%) carried a 19-22 weeks of gestation. The causes for therapeutic termination of pregnancy were risk of life in 8 (13%) pregnant women and risk for physical and mental health in 53 (87%). The most frequent cause the mother considered as risk of life was active systemic lupus erythematosus, and as risk for physical and mental health, fetal congenital malformations incompatible with life including anencephaly and acrania. Misoprostol and uterine curettage were the most often methods (82%, n = 50) used for termination of pregnancy. Conclusions: Cases of therapeutic termination of pregnancy have increased over time at our institution. Most have been due to causes that endangered the mother’s physical and mental health such as fetal congenital malformations incompatible with extrauterine life. Obstetric and perinatology guidelines for therapeutic termination of pregnancy are being formally applied at the Instituto Nacional Materno Perinatal.